2014
DOI: 10.1371/journal.pone.0094093
|View full text |Cite
|
Sign up to set email alerts
|

Rising Tides or Rising Stars?: Dynamics of Shared Attention on Twitter during Media Events

Abstract: “Media events” generate conditions of shared attention as many users simultaneously tune in with the dual screens of broadcast and social media to view and participate. We examine how collective patterns of user behavior under conditions of shared attention are distinct from other “bursts” of activity like breaking news events. Using 290 million tweets from a panel of 193,532 politically active Twitter users, we compare features of their behavior during eight major events during the 2012 U.S. presidential elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 59 publications
5
102
0
Order By: Relevance
“…While eyewitness accounts are important and certainly played a role in disaster coverage of recent times, in the aftermath of such disasters it appears that journalists still turned to governments, officials and businesses; as Lin et al (2014) found in the political sphere, elite voices continue to crowd out more diverse voices when such disastrous events take place.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While eyewitness accounts are important and certainly played a role in disaster coverage of recent times, in the aftermath of such disasters it appears that journalists still turned to governments, officials and businesses; as Lin et al (2014) found in the political sphere, elite voices continue to crowd out more diverse voices when such disastrous events take place.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a study on BBC convergent news of the Haiti earthquake shows that only eight web-stream entries came from 'average people' in Haiti whilst the remaining 42 are attributed either to western NGOs or to westerners who are indirectly touched by the earthquake (Chouliaraki 2010: 316). This is backed up with the recent study by Lin et al (2014), who looked at tweets around the 2012 US presidential election. They concluded that despite the potential for social media to create larger public squares with more diverse voices speaking, occasions for large-scale shared attention appear to undermine this deliberative potential by replacing existing interpersonal social dynamics with increased collective attention to existing 'stars' (Lin et al 2014: 10).…”
Section: This Optimism Has Not Been Realized As Has Been Demonstratementioning
confidence: 98%
“…The Twitter dataset [11] was collected during the U.S presidential election debates held in October 2012. For demonstration purposes, we selected a set of most active users who posted or retweeted the most in the data.…”
Section: Detecting Anomalous Behaviors In Twittermentioning
confidence: 99%
“…Researchers were also able to show that various events during the campaign for the US Presidential election in 2012 were detectable by shifts in user behavior (e.g. Lin et al 2014). These studies show that various offline phenomena lead to shifts in the micro-behavior of users that can be detected in aggregate data.…”
Section: Metrics For the Analysis Of Social Phenomena Based On Twittementioning
confidence: 99%